ANALISIS PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN MEDIA COMMUNICATION TERHADAP KEPUTUSAN PEMBELIAN (Survei pada Lembaga Pendidikan Bahasa Inggris Interactive English Language Center di Surakarta dan Sukoharjo) - Safitri, Natalina Wahyu; Suddin, Alwi; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This research is conducted in order to find out the significance of the influence of (1) brand awareness, (2) brand image and (3) media communication towards the purchasing decision of the consumers of English Education IELC in Surakarta and Sukoharjo. The samples were taken employing the purpossive random sampling and accidental sampling methods. The data were collected through questionnaires using validity and reliability tests. The analysis technique employed the double linear regression, t test, F test, R2 test and classic assumption test. The result of the validity test shows that the research instruments are valid. The result of the realibility test was reliable. The results of the classic assumption test shows that the multicollinearity test, heteroskedasticity test, autocorrelation test, and normality test are all passed. The analysis result shows that Brand Awareness, Brand Image and Media communication all significantly influenced the purchase decision.